Gas analyzer's drift leads to systematic error in maximal oxygen uptake and maximal respiratory exchange ratio determination - Garcia-Tabar, Ibai; Eclache, Jean P.; Aramendi, José F.; Gorostiaga, Esteban M. (Frontiers in Physiology, 2015)
The aim was to examine the drift in the measurements of fractional concentration of oxygen (FO2) and carbon dioxide (FCO2) of a Nafion-using metabolic cart during incremental maximal exercise in 18 young and 12 elderly males, and to propose a way in which the drift can be corrected. The drift was verified by comparing the pre-test calibration values with the immediate post-test verification values of the calibration gases. The system demonstrated an average downscale drift (P < 0.001) in FO2 and FCO2 of -0.18% and -0.05%, respectively. Compared with measured values, corrected average maximal oxygen uptake values were 5-6% lower (P < 0.001) whereas corrected maximal respiratory exchange ratio values were 8-9% higher (P < 0.001). The drift was not due to an electronic instability in the analyzers because it was reverted after 20 minutes of recovery from the end of the exercise. The drift may be related to an incomplete removal of water vapor from the expired gas during transit through the Nafion conducting tube. These data demonstrate the importance of checking FO2 and FCO2 values by regular pre-test calibrations and post-test verifications, and also the importance of correcting a possible shift immediately after exercise.